POLA PERMUKIMAN GUA DI PEGUNUNGAN KENDENG UTARA - Nurani, Indah Asikin (BRIN, 1999)
The cultural potential in Tuban Regency shows varied artifacts, both lithic artifacts, bones, and shells of molluscs in large numbers in relatively thick soil layers. Based on these conditions, it appears that there is a relationship between the settlement period between the cave groups in Bojonegoro and the cave groups in Tuban. It is possible that the caves in Bojonegoro were inhabited during a certain time or season, while the caves in Tuban were inhabited during other seasons. This is evidenced by the different quantity and archaeological qualities.